Motilities and viabilities of separation results of spermatozoa X and Y technique of anode-cathode by in vitro - Musanip Musanip (Jurnal Pijar Mipa, 2023)
Spermatozoa X and Y have different characteristics. Various techniques have been developed to exploit some differences to dissociate spermatozoa carriers of chromosomes X and Y. Technique with cathode-anode in vitro can be expected to be more practical, cheap, easy, and efficient compared to other methods. This research is a pure experimental laboratory with anode-cathode treatment at different time treatments and voltages. The research device is used factorial device with a pattern 2 x 4. The research results indicate that the motilities and viabilities of dissociation of spermatozoa X and Y with anode-cathode by in Vitro are motilities at 30.33% and viabilities at 67%. Result of spermatozoa Y at the cathode with motilities at 33.25% and viabilities at 65.63%. The best quality of spermatozoa Y dissociation in the cathode was obtained by treatment of voltage 1.0 volt for 10 minutes. Time treatment and voltage do not affect the motilities and viabilities of spermatozoa (P > 0.05).